2005
DOI: 10.1111/j.1365-2109.2005.01209.x
|View full text |Cite
|
Sign up to set email alerts
|

Spirulina as a nutrient source in diets for growing sturgeon (Acipenser baeri)

Abstract: The efficiency of diets with the inclusion of Spirulina for Siberian sturgeon weaning has been tested. Three isoproteic and isoenergetic diets were formulated with an increasing level of Indian strain Spirulina (SP 40%, SP 50% and SP 60%); the diets were tested against a control diet without microalgae. The results show that Spirulina inclusion improves growth and that an inclusion level of 50% gave the greatest growth rate, a better favourable feed conversion rate and the highest protein efficiency. The fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
51
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(74 citation statements)
references
References 25 publications
19
51
3
1
Order By: Relevance
“…In the present study, most of the growth characteristics showed increasing trends by the inclusion of 2.5-10 % of the algal meal, whereas further inclusion up to level of 20 % decreased growth performances. This finding agrees with studies on microalga as a substitute for fish meal or soybean meal in diets for silver sea bream (El-Sayed 1994), tilapia (Olvera-Novoa et al 1998), rainbow trout , and sturgeons (Palmegiano et al 2005(Palmegiano et al , 2008. Although a replacement level of 20 % algal meal was taken as the greatest amount of inclusion in the present study, it might likely be expected that higher levels of substitutions render significant declines in the growth indicators.…”
Section: Discussion Growth Performance and Survivalsupporting
confidence: 91%
“…In the present study, most of the growth characteristics showed increasing trends by the inclusion of 2.5-10 % of the algal meal, whereas further inclusion up to level of 20 % decreased growth performances. This finding agrees with studies on microalga as a substitute for fish meal or soybean meal in diets for silver sea bream (El-Sayed 1994), tilapia (Olvera-Novoa et al 1998), rainbow trout , and sturgeons (Palmegiano et al 2005(Palmegiano et al , 2008. Although a replacement level of 20 % algal meal was taken as the greatest amount of inclusion in the present study, it might likely be expected that higher levels of substitutions render significant declines in the growth indicators.…”
Section: Discussion Growth Performance and Survivalsupporting
confidence: 91%
“…The substitution of FM and FO by plant products is a common practice in fish aquaculture feeds (De Francesco et al, 2004;Palmegiano et al, 2005). Unfortunately, the use of plant products can lead to adverse effects, essentially attributable to their content of anti-nutritional factors and/or unpalatable compounds, inappropriate fatty acid (FA) profile, and shortage of essential amino acids (Gatlin et al, 2007;Gai et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…SP has been evaluated widely as fresh meal for mollusc bivalve and fish larvae (Harel et al, 2002;Lu et al, 2002) or as raw meal for juveniles and adults (Nandesha et al, 2001;Takeuki et al, 2002;Palmegiano et al, 2005;Palmegiano et al, 2008).…”
Section: Introductionmentioning
confidence: 99%